The Use of Cone Beam Computed Tomography (CBCT) to Determine Supernumerary and Impacted Teeth Position in Pediatric Patients: A Case Report - Hossein Nematolahi; Hamed Abadi; Zahra Mohammadzade; Mostafa Soofiani Ghadim (Tabriz University of Medical Sciences, 2013)
A case of a compound odontoma which caused delayed eruption of right maxillary central incisor in a ten year old girl is presented with clinical and radiographic findings. The patient presented with complaint of a hard painless swelling in the right anterior region of the maxilla and absence of right maxillary central incisor. After clinical examination, periapical and occlusal radiographs of the mentioned region were taken. Impacted maxillary right central incisor was seen malformed shape on the intraoral radiographs. After taking a cone beam computed tomography (CBCT) a compound odontoma associated with the labial aspect of impacted maxillary right central incisor was diagnosed and then removed by simple local excision under local anesthesia. The removal of the odontoma was followed by forced eruption of the impacted central incisor. After three months the tooth returned to its original position.